2023
DOI: 10.1038/s41467-023-37997-6
|View full text |Cite
|
Sign up to set email alerts
|

Polyfluorinated crosslinker-based solid polymer electrolytes for long-cycling 4.5 V lithium metal batteries

Abstract: Solid polymer electrolytes (SPEs), which are favorable to form intimate interfacial contacts with electrodes, are promising electrolyte of choice for long-cycling lithium metal batteries (LMBs). However, typical SPEs with easily oxidized oxygen-bearing polar groups exhibit narrow electrochemical stability window (ESW), making it impractical to increase specific capacity and energy density of SPE based LMBs with charging cut-off voltage of 4.5 V or higher. Here, we apply a polyfluorinated crosslinker to enhance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…Definitely the chemical stability of the interface between polymer electrolyte and electrodes needs to be improved to enhance the cyclability. Recent advances on designing SPEs for long-cycling batteries include polyfluorinated cross-linking, composite of dielectric nanowires and PVDF matrix to form heterojunction structure, and combination of high molecular weight PVDF and stable interface layer . In addition, the role of Li-ion salts needs to be carefully evaluated since it was found that a significant change of electrochemical stability window of polymer electrolytes can occur depending upon the formation of polymer/salt complexes .…”
Section: Resultsmentioning
confidence: 99%
“…Definitely the chemical stability of the interface between polymer electrolyte and electrodes needs to be improved to enhance the cyclability. Recent advances on designing SPEs for long-cycling batteries include polyfluorinated cross-linking, composite of dielectric nanowires and PVDF matrix to form heterojunction structure, and combination of high molecular weight PVDF and stable interface layer . In addition, the role of Li-ion salts needs to be carefully evaluated since it was found that a significant change of electrochemical stability window of polymer electrolytes can occur depending upon the formation of polymer/salt complexes .…”
Section: Resultsmentioning
confidence: 99%
“…19 However, the effect of high/low temperatures on polymer-based electrolytes is multi-dimensional, not only including the physical and electrochemical properties of electrolytes (low temperature ionic conductivity and thermal stability), but also relating to the electrode–electrolyte interface compatibility (interface stability and destruction). 20–23 Numerous studies have attempted to overcome these limitations. For instance, Yu and coworkers demonstrated that the ionic conductivity of polymer-based electrolytes could be improved by introducing different dipoles; the as-prepared poly(vinyl ethylene carbonate) (PVEC) based polymer electrolyte contained two kinds of dipoles (CO and C–O) and achieved a high ionic conductivity of 0.4 mS cm −1 @−15 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high theoretical specific capacity (3860 mAh g –1 ) and the most negative potential (−3.04 V vs SHE), lithium metal anode (LMA) , has been regarded as a most welcomed anode candidate for the high-energy-density battery . However, the development of LMA is severely limited by the uncontrollable Li dendrite growth and the unstable solid electrolyte interphase (SEI), which requires strategy innovation. The capabilities and interface of the substrate have a critical impact on the reversibility of LMA in tutoring the Li nucleation and deposition behavior, especially in anode-free lithium metal battery configurations. The copper (Cu) foil, as the only commercialized negative current collector for Li-ion batteries, possesses many advantages, including ideally good conductivity, mechanical properties, low cost, and manufacturing compatibilities.…”
Section: Introductionmentioning
confidence: 99%